Production of high-carbon-number bio-aviation fuels from furans using sulfated zirconia and silica-alumina aerogel catalysts - Yati, Indri; Kang, Jisong; Noh, Haeun; Choo, Hyunah; Choi, Jae-Wook; Suh, Dong Jin; Ha, Jeong-Myeong (Elsevier BV, 2024)
Lignocellulose can help produce fuels in biorefineries through its fractionated components such as cellulose, hemicelluloses, and lignin. For instance, hemicellulose-derived xylose has been studied for obtaining petroleumsubstituting fuels. Therefore, in this study, catalytic hydroalkylation/alkylation (HAA) of xylose-derived 2-methylfuran (2-MF) with butanal was targeted to selectively produce high-carbon-number diesel fuels. To that end, silica-alumina (SiAl) aerogels with different Si/Al ratios and a series of sulfated zirconia (SZ) compounds calcined at various temperatures were prepared as catalysts to overcome the limitations of conventional hazardous homogeneous acid catalysts. The activity of the SiAl catalysts in forming the desired HAA product, 5,5bissylvylbutane (denoted as BB), was found to be directly related to the number of acid sites and acid density. Moreover, increasing the Si/Al molar ratio, which reduced the acid density and number of acid sites, led to lower 2-MF conversions and BB yields. The optimal 2-MF conversion and BB yield with the SiAl catalysts (67 % and 45 %, respectively) were achieved using a Si/Al ratio of 8:2 mol/mol. Furthermore, SZ calcined at 700 degrees C (denoted as SZ-700) exhibited the highest activity among the SZ catalysts (72 % 2-MF conversion, 63 % BB yield), despite having the fewest acid sites and lowest acid density. This was presumably because of the physical structure of SZ700, which featured mixed monoclinic and tetragonal phases, many oxygen vacancies, and a large accessible external surface area, which facilitated the HAA reactions. Hydrogenation and hydrodeoxygenation (HDO) of BB were performed thereafter using Pd/C and Ru/SiO2-Al2O3 catalysts, respectively. The resulting deoxygenated hydrocarbons comprised 15.1 % light hydrocarbons (C4-C8) and 83.1 % heavier hydrocarbons (C9-C20). Simulated distillation analysis of the post-HDO product distribution indicated that the liquid-phase product contained 70 % high-carbon-number bio-aviation fuels.